Patient characteristics and pharmacologic treatment patterns in antifibrotic-treated patients with fibrosing interstitial lung diseases: real-world results from a claims database - Yasuhiro Kondoh; Tomohiro Ito; Hana Kimura; Haikun Bao; Masataka Kuwana (BMC Pulmonary Medicine)
Abstract Background Antifibrotics have been approved for use in many countries, including Japan, based on the results of several phase III clinical trials in patients with IPF, SSc-ILD, and PPF, which showed slower lung function decline with antifibrotic treatment. There is a paucity of information on the real-world use of antifibrotics in clinical practice. Methods Baseline characteristics, comorbidities, and drugs used prior to and concomitant with antifibrotics were collected for patients with IPF, SSc-ILD, and PPF using a health insurance claims database in Japan from 1 January 2013 to 30 June 2023. Descriptive statistics were generated for all study variables. Results This study included 657 nintedanib users with IPF; 418 pirfenidone users with IPF; 4160 nintedanib users with PPF; 18,403 users of glucocorticoids/immunosuppressants for ILD treatment with PPF; 676 nintedanib users with SSc-ILD; and 698 users of glucocorticoids/immunosuppressants for ILD treatment with SSc-ILD. At index, pirfenidone users with IPF were the oldest (mean [SD] 74.8 [7.3] years), and nintedanib users with SSc-ILD were the youngest (mean [SD] 65.6 [11.7] years). In nintedanib users with IPF, 76.7% were prescribed nintedanib as monotherapy, and 75.6% of pirfenidone users were prescribed pirfenidone, as monotherapy. In patients with IPF, 75.2% were prescribed nintedanib, and 76.1% were prescribed pirfenidone, as first-line therapy. In patients with SSc-ILD, 34.9% were prescribed nintedanib as monotherapy for ILD treatment, and 38.6% as first-line therapy. Approximately half of patients with PPF were prescribed nintedanib concomitantly with other glucocorticoids/immunosuppressant drugs, and after one or more glucocorticoids/immunosuppressant drugs. The most common concomitant drug in all patient groups was glucocorticoids. In patients with IPF, 18.6% of nintedanib users and 18.2% of pirfenidone users were prescribed glucocorticoids concomitantly. Concomitant glucocorticoid use was 52.7% for nintedanib users with SSc-ILD, and 44.1% for nintedanib users with PPF. Conclusions These results provide real-world evidence of antifibrotic use in clinical practice. Most patients with IPF were prescribed antifibrotics as monotherapy for ILD treatment whereas antifibrotics were used concomitantly with glucocorticoids/immunosuppressants in many patients with SSc-ILD and PPF. While most patients with IPF were prescribed antifibrotics as first-line therapy, patients with SSc-ILD and PPF were more likely to be prescribed nintedanib as second-line or later-line treatment after glucocorticoids/immunosuppressants.